Integration of microbattery with thin-film electronics for constructing an integrated transparent microsystem based on InGaZnO - Bin Jia; Chao Zhang; Min Liu; Zhen Li; Jian Wang; Li Zhong; Chuanyu Han; Ming Qin; Xiaodong Huang (Nature Communications, 2023)
Abstract A full integration of miniaturized transparent energy device (lithium-ion battery), electronic device (thin-film transistor) and sensing device (photodetector) to form a monolithic integrated microsystem greatly enhances the functions of transparent electronics. Here, InGaZnO is explored to prepare the above devices and microsystem due to its multifunctional properties. A transparent lithium-ion battery with InGaZnO as anode (capacity~9.8 μAh cm−2) is proposed as the on-chip power source. Then, thin-film transistor with InGaZnO as channel (mobility~23.3 cm2 V−1 s−1) and photodetector with InGaZnO as photosensitive layer (responsivity~0.35 A W−1) are also prepared on the substrate for constructing an fully integrated transparent microsystem. Each device displays acceptable performance. Moreover, alternating-current signals can be successfully charged into the lithium-ion battery by using the thin-film transistor as the on-chip rectifier and also the photodetector works well by using the charged battery as the on-chip power, demonstrating collaborative capabilities of each device to achieve systematic functions.